Comparative sub-cellular proteome analyses reveals metabolic differentiation and production of effector-like molecules in the dieback phytopathogen Phytophthora cinnamomi. - Andronis, Christina; Jacques, Silke; Lipscombe, Richard; Tan, Kar-Chun (2022)
Phytopathogenic oomycetes pose a significant threat to global biodiversity and food security. The proteomes of these oomycetes likely contain important factors that contribute to their pathogenic success, making their discovery crucial for elucidating pathogenicity. Phytophthora cinnamomi is a root pathogen that causes dieback in a wide variety of crops and native vegetation world-wide. Virulence proteins produced by P. cinnamomi are not well defined and a large-scale approach to understand the biochemistry of this pathogen has not been documented. Soluble mycelial, zoospore and secreted proteomes were obtained and label-free quantitative proteomics was used to compare the composition of the three sub-proteomes. A total of 4635 proteins were identified, validating 17.7% of the predicted gene set. The mycelia were abundant in transporters for nutrient acquisition, metabolism and cellular proliferation. The zoospores had less metabolic related ontologies but were abundant in energy generating, motility and signalling associated proteins. Virulence-associated proteins were identified in the secretome such as candidate effector and effector-like proteins, which interfere with the host immune system. These include hydrolases, cell wall degrading enzymes, putative necrosis-inducing proteins and elicitins. The secretome elicited a hypersensitive response on the roots of a model host and thus suggests evidence of effector activity.